Monosynaptic Stretch Reflex Fails to Explain the Initial Postural Response to Sudden Lateral Perturbations - Mühlbeier, Andreas; Puta, Christian; Boström, Kim J.; Wagner, Heiko (Frontiers in Human Neuroscience, 2017)
Postural reflexes are essential for locomotion and postural stability, and they are supposed to play an important role in the etiology of chronic back pain. It has recently been theoretically predicted and with the help of unilateral perturbations of the trunk experimentally confirmed that the sensorimotor control must lower the reflex amplitude for increasing reflex delays to maintain spinal stability. The underlying neuromuscular mechanism for the compensation of postural perturbations, however, is not yet fully understood. In this study, we applied unilateral and bilateral sudden external perturbations to the trunk of healthy subjects and measured the muscular activity and the movement onset of the trunk. We found that the onset of the trunk muscle activity is prior to, or coincident with, the onset of the trunk movement. Additionally, the results of our experiments imply that the muscular response mechanism integrates distant sensory information from both sides of the body. These findings rule out a simple monosynaptic stretch reflex in favor of a more complex polysynaptic postural reflex mechanism to compensate postural perturbations. Moreover, the previously predicted negative correlation between reflex delay and reflex gain was confirmed also for bilateral perturbations.